Slowly Sinking Particles Underlie Dissolved Iron Transport Across the Pacific Ocean. Issue 4 (19th April 2021) - Misumi, K.; Nishioka, J.; Obata, H.; Tsumune, D.; Tsubono, T.; Long, M. C.; Lindsay, K.; Moore, J. K.
Abstract: Continental shelf sediments are an important source of iron (Fe) in the oceans. Observational data suggest that basin‐scale transport of sedimentary sourced Fe accompanies the ventilation of the intermediate layer in the North Pacific. Here we use a marine biogeochemical model to explore the Fe transport mechanism with a focus on the role of sinking particles. The lateral penetration of sedimentary sourced Fe was best simulated when we assumed a short desorption and disaggregation length scale of Fe from sinking particles. The simulation results indicated that Fe is laterally transported mainly through interactions with particles with sinking velocities of 180–460 m yr −1 ; these velocities are two orders of magnitude slower than typical sinking rates of marine aggregates determined from mass flux measurements. Slowly sinking particles drive the basin‐scale transport of Fe by prolonging its residence time and by injecting sedimentary sourced Fe supplied originally to less dense waters into the intermediate layer water across isopycnal surfaces. A large amount of Fe from shelf sediments of the Okhotsk and Bering Seas is exported to the North Pacific through this particle interaction. These results highlight a biogeochemical linkage between the marginal seas and ocean basins that has been overlooked in global ocean models. Plain Language Summary: Iron (Fe) is an essential micronutrient for marine phytoplankton, and understanding its source and cycle in the ocean is essential for understanding the future carbon cycle and thus climate change. Although continental shelf sediments have been thought to be a major Fe source, how Fe, which is hardly soluble in seawater, is transported to the open ocean is still unclear. We used a numerical model simulating marine biogeochemical cycles to investigate the transport mechanism and found that Fe is transported long distances in association with slowly sinking particles. Our results suggest that a large amount of the Fe in North Pacific waters comes from marginal sea shelf sediments. Key Points: Slowly sinking particles extend the residence time of iron in the ocean and support the long‐range transport Adsorption and aggregation, and desorption and disaggregation processes likely control generation of iron‐rich and slowly sinking particles Substantial amounts of iron supplied from continental shelf sediments in the marginal seas are exported to the North Pacific